Dinamika Pemanfaatan Harta Pusako di Minangkabau dalam Pespektif Teori Modal Sosial dan Tindakan Sosial: Studi Kasus Kecamatan Sungai Tarab - Vidi Rifardo; Nofialdi Nofialdi; Ulya Atsani; Elimartati Elimartati; Sri Yunarti (IDRIS Darulfunun Institute, 2026)
The main problem in this research is to discuss the forms and dynamics of the utilization of high-ranking heirloom assets, the factors that encourage the community to utilize high-ranking heirloom assets, and the perspectives of traditional leaders on these dynamics in Sungai Tarab District, Tanah Datar Regency. The research method used is field research with a qualitative approach. Data sources in this study consist of primary and secondary sources. Data collection techniques were conducted through interviews and documentation. Data analysis techniques used were data reduction, data presentation, and conclusion drawing. The technique used to ensure data validity was triangulation of data sources. The results indicate that the utilization of high-ranking heirloom assets in Sungai Tarab is a form of instrumental rational social action, where management is carried out as a means to meet family needs, such as food, education costs, social and customary needs, and other economic needs. This utilization dynamic is driven by economic pressures and changes in social values that influence interaction patterns within the community. From a social capital perspective, the utilization of high-ranking heirloom assets reflects a shift in the function of trust bonds and networks among community members, where the weakening of customary oversight has led to the strengthening of individual interests over collective ones. However, according to Minangkabau custom, this use remains permissible as long as it does not diminish collective ownership of the clan, is carried out through deliberation as a manifestation of healthy social capital, and remains within the framework of the ganggam bauntuak concept.